Prevalence and Patterns of Elderly Abuse in Family Environment: A Cross-Sectional Study of Hetauda Sub-Metropolitan City - Timalsina, Keshab Prasad (International Research Journal of MMC, 2023)
The primary goal of this study is to investigate the relationship between elderly people's socioeconomic characteristics and the average rank of elderly abuse patterns. The study was primarily concerned with quantitative research and employed a cross-sectional survey method. From a population of 16,489 in Hetauda Sub-metropolitan City, 412 elderly people were chosen at random. To collect data, face-to-face interviews with structured interview schedules were used. A pilot survey was conducted to ensure validity and reliability in data. In the study, data was analysed using univariate and bivariate frequency distributions, as well as non-parametric tests. According to the study, the prevalence of overall abuse was 35.90% and psychological abuse was observed high among others. The most common types of abuse were moderate psychological abuse (43.8%), neglect (60.5%), and overall abuse (57.8%). Mild economic abuse accounted for 60%, while other types of abuse accounted for 79.4%. The study also looked at the link between abuse and gender, and found statistically insignificant differences (p>0.05). However, there was a significant difference (p<0.05) in the prevalence of psychological and overall abuse based on property ownership, whereas other patterns revealed no significant differences (p>0.05). Except for psychological and overall abuse, dependency status had no significant impact on the occurrence of elder abuse patterns (p>0.05). Except for certain participants, the prevalence of elderly abuse was high. Psychological, economic, and overall abuse varied significantly by age group, but neglect and other forms did not (p>0.05). Except for psychological abuse, family size and income level were found to have significant differences in abuse patterns. The study's findings highlight the importance of targeted interventions and policies to prevent and address elder abuse, particularly among vulnerable populations. To address the identified disparities, comprehensive measures that prioritise the well-being and safety of vulnerable elders must be implemented.